2009
DOI: 10.1130/b26450.1
|View full text |Cite
|
Sign up to set email alerts
|

Provenance of Upper Cretaceous-Paleogene sandstones in the foreland basin system of the Sierra Madre Oriental, northeastern Mexico, and its bearing on fluvial dispersal systems of the Mexican Laramide Province

Abstract: Sandstone petrography and detrital zircon U-Pb analysis of Upper Cretaceous-Paleogene sandstones in the foreland basin of the Sierra Madre Oriental in northeastern Mexico indicate long-distance sediment transport from arc, basement, and thrust-belt sources lying to the west, northwest, and south. The basin fi ll, termed the Difunta Group, consists of sublitharenites, litharenites, feldspathic litharenites, and lithic arkoses derived from mixed sources that included sedimentary rocks, magmatic arc rocks, and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(47 citation statements)
references
References 54 publications
1
44
0
2
Order By: Relevance
“…Radiometric data provide a critical means for understanding the geological history of deposits and their potential sediment source regions. Radiometric provenance techniques supplement mineralogical information acquired by more traditional petrographic methods, such as light and heavy mineral analysis or whole-rock geochemistry, providing a more complete and accurate characterization of sediment provenance (e.g., Dickinson and Gehrels , 2008a, 2008b, 2009aLawton et al, 2009). Young detrital zircon grain ages have the added potential of indicating maximum depositional ages of a stratigraphic unit (e.g., Dickinson and Gehrels, 2009b), which can indicate true depositional age, if syndepositional volcanism took place in the drainage network providing sediment to a basin or if zircons derived from eruptive ash fell into the basin.…”
Section: Introductionmentioning
confidence: 99%
“…Radiometric data provide a critical means for understanding the geological history of deposits and their potential sediment source regions. Radiometric provenance techniques supplement mineralogical information acquired by more traditional petrographic methods, such as light and heavy mineral analysis or whole-rock geochemistry, providing a more complete and accurate characterization of sediment provenance (e.g., Dickinson and Gehrels , 2008a, 2008b, 2009aLawton et al, 2009). Young detrital zircon grain ages have the added potential of indicating maximum depositional ages of a stratigraphic unit (e.g., Dickinson and Gehrels, 2009b), which can indicate true depositional age, if syndepositional volcanism took place in the drainage network providing sediment to a basin or if zircons derived from eruptive ash fell into the basin.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies (e.g. Pessagno 1969;Salvador 1991;Sohl et al 1991;Hernandez-Jaúregui 1997;Goldhammer 1999;Lawton et al 2009;Gray and Lawton 2011) indicate that the vast majority of clastic material found in turbidites deposited in cretaceous foreland basins are derived from Cretaceous carbonates progressively uplifted from western to eastern Mexico. On the western side of the studied section, in the ZB, the age of the Soyatal Formation (syn-tectonic turbidites) is constrained to be between middle Turonian and lower Campanian (Kiyokawa 1981; Hernández-Jaúregui 1997, Figure 3).…”
mentioning
confidence: 98%
“…Cross section after Hon (2001). lithic grains were derived from an uplifted hinterland that exposed Lower Cretaceous carbonates to the west (e.g., Lawton et al, 2009).…”
Section: Evidence For Timing Of Contractional Structuresmentioning
confidence: 99%